PENGARUH PROFITABILITAS TERHADAP PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rustan Rustan; Endang Winarsih (Universitas Muhammadiyah Makassar, 2018)
Research aims to determine the influence of ownership structures, financial leverage, and profitability of profit leveling. Data collection In this research is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The sampling method used in this research is the purposive sampling method, so that a sample of 13 companies can be obtained. While the data processing method used is multiple regression analysis. The results of this research show that the variable ownership structure has a positive and significant effect on profit leveling, the financial leverage variable is positive and significant to the profit leveling, and the profitability variable Significant impact on profit leveling.